Sexual health interventions among early adolescents: an integrative review - Monrudee Chokprajakchad; Rutja Phuphaibul; Renee Evangeline Sieving (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - Adolescent pregnancy and sexually transmitted infections including HIV are important public health issues in many countries around the world. The trend is escalating among adolescents of younger ages. Many programmes aim to prevent adolescent sexual risk behaviours associated with these health outcomes. The purpose of this paper is to describe and analyse methodological and substantive features of research on interventions to delay the initiation of sexual intercourse and prevent other sexual risk behaviours among early adolescents. Design/methodology/approach - The review includes studies published between 2006 and 2017 that appear in Thai and international databases. Findings - A total of 33 studies met specified review criteria. Of the studies reviewed, 14 used randomized control designs, 16 used quasi-experimental designs and three used a pre-test, post-test design. Sample sizes ranged from 64 to 4,776 subjects; nearly two-thirds of the studies (n = 22) included multiple follow-up surveys. The programmes evaluated in these studies can be grouped into three categories: abstinence-based sexuality education programmes (n = 12), comprehensive sexuality education programmes (n = 13) and youth development programmes designed for early adolescents (n = 10). In total, 22 programmes reviewed were effective in changing targeted adolescent psychosocial and/or behavioural outcomes. Research limitations/implications - One of the limitations encountered in this study involved the search in library databases published only in Thai and English. Due to the limitation of searching library databases included in the review that reported the effects and differences among the included studies. Moreover, the search included publications consisted of heterogeneous designs and purpose with reports of different types of outcomes made it impossible to compare effect sizes. Practical implications - The knowledge gained can be used to design and implement effective sexual health promotion programmes for early adolescents. Moreover, the findings can be applied as a guideline for health provider working in a schools, communities and adolescent health services. Recommendations for future studies are needed to consider methodological and substantive characteristics as well as the people who are involved in youth sexual health outcomes. Social implications - It is necessary for government to develop a policy for encouraging parents to be aware and participate in solving the problems. Originality/value - The review indicated that the positive effects of parental involvement and technology media as a programme material on the psychosocial and behavioural outcomes.